Waste Management Policy Of Pontianak City in Post-Pandemic Covid-19 Based on Environmental Democracy - Zhan, Fuzy Firda; Elyta, Elyta; Nge, Herri Junius; Jalius, As'ad Albatroy; Padilah, Ahirul Habib (Jurusan Ilmu Politik, FISIP, Universitas Andalas, 2024)
The Covid-19 pandemic that has hit Indonesia since the beginning of 2020 has had a multi-sectoral impact, including in the environmental sector. At the beginning of the pandemic, the amount of waste generated in Pontianak City had decreased but then increased again. This study was conducted to analyze waste management policies in Pontianak City in Post-Pandemic Covid-19 based on Environmental Democracy. The method used in this study is a descriptive method with a qualitative approach. The data were obtained from interviews with related parties and by conducting literature studies. Environmental democracy is a government system with the highest sovereignty over the people and places human interests in a position that goes hand in hand with environmental sustainability. This study found that waste management policies in Pontianak City can be carried out with Environmental Democracy through the provision of information related to waste management in Pontianak City which is more actual and easily accessible, providing participation space for the community to increase awareness and actively participate in policy formulation or regulations to reducing waste generation, and strengthening access to justice including regarding sanctions or fines for violations of pollution due to waste generation.